INTRODUCTION TO THE 35TH FICE WORLD CONGRESS SPECIAL ISSUE - Anglin, James P.; Gulamhusein, Shemine A.; Schneider, Alexander (International Journal of Child, Youth and Family Studies, 2025)
The 35th World Congress of FICE-International, “Shaping Tomorrow’s Care for Children and Youth: Quality and Innovation in Alternative Care”, was held in Split, Croatia on October 23 to 25, 2024. The aim of this congress was to explore and promote innovative approaches to elevate child well-being in alternative care and child protection through collaborative efforts. This special issue of the International Journal of Child, Youth and Family Studies (IJCYFS) includes 14 articles based on presentations and discussions in Split. The authors represent 12 countries, thereby offering truly international perspectives, programs, and policies related to the conference themes.